2019
DOI: 10.1002/bem.22220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiofrequency and Extremely Low‐Frequency Field Levels at Children's Playground Sites in Greece From 2013 to 2018

Abstract: in-situ measurements of radiofrequency (RF) electromagnetic fields (EMF) and extremely low-frequency (ELF) electric and magnetic fields in 317 existing and under-construction children's playground facilities, in 16 municipalities all over Greece, were carried out by the Greek Atomic Energy Commission (EEAE). These measurements were conducted following legislative framework established in 2009, which requires that compliance with the established exposure limits for EMFs should be verified in playground areas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Our findings confirm the low EMF-RF exposure levels at outdoor environments and specifically at school buildings not only in Greece, but also internationally [27], [32], [52], [53], [54], [55], [56]. More specifically, the studies realized in Greece have so far shown similar results [58], [59] on the overall average value of electromagnetic radiation at children places (e.g. schools, playgrounds, etc.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings confirm the low EMF-RF exposure levels at outdoor environments and specifically at school buildings not only in Greece, but also internationally [27], [32], [52], [53], [54], [55], [56]. More specifically, the studies realized in Greece have so far shown similar results [58], [59] on the overall average value of electromagnetic radiation at children places (e.g. schools, playgrounds, etc.…”
Section: Discussionsupporting
confidence: 88%
“…The rest of the studies cited in Table 6 refer to measurements that were conducted outdoors and in the vicinity of places where children tend to spend most of their time, such as schools, kindergartens, and playgrounds. Bhatt et al [3], Yener et al [5], and Gallastegi et al [4] conducted measurements in Australia, Turkey, and Spain, respectively, whereas the studies by Christopoulou and Karabetsos [10], Kiouvrekis et al [11], as well as our work, refer to playgrounds and schools in Greece. It may be verified from Table 6 that the recent work by Kiouvrekis et al [11] and the present study report greater median values of the measured E-field strength than the studies performed a few years ago [3,4,10].…”
Section: Comparisonsmentioning
confidence: 77%
“…Information about RF exposure levels in environments relevant to children, such as schools, kindergartens, and playgrounds, may be found in the literature [3][4][5][6][7][8][9][10][11], but, generally, the investigation of children's EMF exposure is somewhat limited. Outdoor and indoor environmental, as well as personal, RF exposure has been examined in places where children are mostly present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest RF exposure in densely populated areas was 7.1% of the guideline's limits. In the Greek study [Christopoulou and Karabetsos, 2019] concerning RF exposure in playgrounds sites, the median values for the urban environment were 0.244 and 0.229 V/m in the suburban. Gajsek et al [2015] results showed that the mean value of electric field strength ranged between 0.08 V/m (urban, Austria) and 1.80 V/m (close to microcells, UK).…”
Section: Discussionmentioning
confidence: 99%